Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1148/radiology.199.3.8637994
|View full text |Cite
|
Sign up to set email alerts
|

Effects of training and experience in interpretation of emergency body CT scans.

Abstract: Experience appeared to decrease discrepancy rates. Trainees were more likely to miss findings than to read normal scans as abnormal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
39
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(47 citation statements)
references
References 0 publications
5
39
2
Order By: Relevance
“…This finding is not intuitive, because error rates would be expected to decrease with more experience. Similar traineelevel patterns of discrepancies have been described by other researchers with body CT (major discrepancies) 16 and head CT 5 interpretations. Because of the small number of cases read by residents in this study, bias from sampling error cannot be discounted as a cause.…”
Section: Discussionsupporting
confidence: 84%
“…This finding is not intuitive, because error rates would be expected to decrease with more experience. Similar traineelevel patterns of discrepancies have been described by other researchers with body CT (major discrepancies) 16 and head CT 5 interpretations. Because of the small number of cases read by residents in this study, bias from sampling error cannot be discounted as a cause.…”
Section: Discussionsupporting
confidence: 84%
“…First, the various rates of discordance may be due, in part, to the varying prevalence of CT abnormalities. Several studies have reported that the proportion of abnormal studies influences concordance, because the discordant rate for abnormal studies is higher than for normal studies (3,13). The proportion of abnormal scans in our series (86.7%) was markedly higher than the 35%-42% rate of positive findings described in previous studies (2-4).…”
Section: Discussioncontrasting
confidence: 70%
“…Its high specificity and sensitivity were maintained even when reported by an on-call radiology registrar and were comparable to results obtained by experienced consultant radiologists. In contrast, a previous study showed that interpretation of CT scans in the emergency setting, both of trauma and nontrauma injuries, was related to the level of training of the radiologist 25 .…”
Section: Discussionmentioning
confidence: 69%